Neutron scattering shows a droplet of oleic acid at the center of the BAMLET complex. Issue 7 (22nd April 2017) - Rath, Emma M.; Duff, Anthony P.; Gilbert, Elliot P.; Doherty, Greg; Knott, Robert B.; Church, W. Bret
ABSTRACT: The anti‐cancer complex, Bovine Alpha‐lactalbumin Made LEthal to Tumors (BAMLET), has intriguing broad‐spectrum anti‐cancer activity. Although aspects of BAMLET's anti‐cancer mechanism are still not known, it is understood that it involves the oleic acid or oleate component of BAMLET being preferentially released into cancer cell membranes leading to increased membrane permeability and lysis. The structure of the protein component of BAMLET has previously been elucidated by small angle X‐ray scattering (SAXS) to be partially unfolded and dramatically enlarged. However, the structure of the oleic acid component of BAMLET and its disposition with respect to the protein component was not revealed as oleic acid has the same X‐ray scattering length density (SLD) as water. Employing the difference in the neutron SLDs of hydrogen and deuterium, we carried out solvent contrast variation small angle neutron scattering (SANS) experiments of hydrogenated BAMLET in deuterated water buffers, to reveal the size, shape, and disposition of the oleic acid component of BAMLET. Our resulting analysis and models generated from SANS and SAXS data indicate that oleic acid forms a spherical droplet of oil incompletely encapsulated by the partially unfolded protein component. This model provides insight into the anti‐cancer mechanism of this cache of lipid. The model also reveals a protein component "tail" not associated with the oleic acid component that is able to interact with the tail of other BAMLET molecules, providing a plausible explanation of how BAMLET readily forms aggregates. Proteins 2017; 85:1371–1378. © 2017 Wiley Periodicals, Inc.